Profil Pemecahan Masalah Perbandingan Senilai Ditinjau dari Kecerdasan Logis Matematis Siswa Kelas VIII SMPN 19 Palu - Afif Ahmad; Fajriani; Muh. Rizal; Bakri M (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Students still experience difficulties in solving story problems on the topic of equivalent comparisons, so a study is needed regarding problem-solving profiles based on logical-mathematical intelligence. This study aims to describe the problem-solving profiles of equivalent comparisons viewed from the logical-mathematical intelligence of eighth-grade students at SMPN 19 Palu. The study used a descriptive qualitative approach. The subjects of the study consisted of two students who were selected purposively based on the results of Olivia's (2009) logical-mathematical intelligence questionnaire, namely one student in the high category (AST) and one student in the low category (PTR). Data were collected through problem-solving tests and in-depth interviews, then analyzed using an interactive model that includes data condensation, data presentation, and conclusion drawing. The results showed that AST was able to carry out all stages of problem-solving according to Polya completely and obtained correct answers (12 liters). In contrast, PTR was only able to fulfill the stage of understanding the problem, while at the stages of formulating plans, implementing solutions, and re-checking, they still experienced conceptual errors resulting in incorrect answers (5.333 liters). These findings indicate that students with high logical-mathematical intelligence have a more systematic and accurate problem-solving profile than students with low logical-mathematical intelligence.